2017
DOI: 10.1182/blood-2017-01-759258
|View full text |Cite
|
Sign up to set email alerts
|

The effect of variation in donor platelet function on transfusion outcome: a semirandomized controlled trial

Abstract: The effect of variation in platelet function in platelet donors on patient outcome following platelet transfusion is unknown. This trial assessed the hypothesis that platelets collected from donors with highly responsive platelets to agonists in vitro assessed by flow cytometry (high-responder donors) are cleared more quickly from the circulation than those from low-responder donors, resulting in lower platelet count increments following transfusion. This parallel group, semirandomized double-blinded trial was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Underlying causes can be patient-associated factors, such as fever, medication, sepsis, or patient anti-PLT antigen (HPA, human PLT antigen) antibodies, or can otherwise be due to the increased consumption of PLTs within the scope of the desired hemostasis [2, 3]. In contrast, PLT refractoriness can be product-related and associated with PLT-inherent functional variations due to the habitual and physiological conditions of the donors [4]. The manufacturing process may also impact PLT functionality [5].…”
Section: Introductionmentioning
confidence: 99%
“…Underlying causes can be patient-associated factors, such as fever, medication, sepsis, or patient anti-PLT antigen (HPA, human PLT antigen) antibodies, or can otherwise be due to the increased consumption of PLTs within the scope of the desired hemostasis [2, 3]. In contrast, PLT refractoriness can be product-related and associated with PLT-inherent functional variations due to the habitual and physiological conditions of the donors [4]. The manufacturing process may also impact PLT functionality [5].…”
Section: Introductionmentioning
confidence: 99%
“…28 The differences in these findings may be related to heterogeneity among the recipients or the PLT donors. 29 Fewer studies have been published that explore a similar association in children. Given the differences in physiology and etiologies of critical illness that exist between children and adults, pediatric patients may have different clinical outcomes associated with the storage age of the PLT concentrates.…”
Section: Discussionmentioning
confidence: 99%
“…[32, 38, 39] Moreover, recent work by Kelly et al ., showed that the ability of platelet apheresis units to increase platelet count in non-bleeding cancer patients with thrombocytopenia was independent of the degree of platelet function as measured by aggregometry, P-selectin expression and fibrinogen binding. [40] Thus, perhaps as long as patients have a threshold concentration of functional platelets in circulation, the transfusion of additional platelets, even though they may exhibit reduced absolute activity, may be sufficient to stop bleeding. In this setting, the reactivity of the platelets within platelet apheresis units may be secondary to the ability to rapidly transport platelet apheresis units to patients at risk of hemorrhage.…”
Section: Discussionmentioning
confidence: 99%